Serum soluble CD163 and proinflammatory chemokines may be biomarkers of the onset of adverse events in dabrafenib plus trametinib combination therapy for advanced melanoma. Issue 1 (22nd November 2020) - Amagai, Ryo; Fujimura, Taku; Muto, Yusuke; Kambayashi, Yumi; Furudate, Sadanori; Ohuchi, Kentaro; Okuma, Takami; Hashimoto, Akira; Aiba, Setsuya
Abstract: Various adverse events (AEs) have been reported to occur at a high rate in patients treated with dabrafenib plus trametinib (D + T) combination therapy. Among such AEs, the incidence of pyrexia was highest among the series of AEs in patients treated with D + T combination therapy. Although little is known about the mechanisms of pyrexia caused by D + T combination therapy, a recent report suggested that sCD163, as well as interferon‐inducible chemokines (CXCL9, CXCL10, CXCL11), might correlate with pyrexia caused by encorafenib plus binimetinib combination therapy. In addition to these soluble factors, CXCL5 is a biomarker for predicting immune‐related AEs in melanoma patients treated with nivolumab. From the above findings, we hypothesized that these soluble factors might also correlate with the onset of AEs in D + T combination therapy. The serum levels of sCD163 were increased in patients with pyrexia in parallel with their severity, whereas the serum levels of CXCL5 were increased in patients without pyrexia. Moreover, increased levels of CXCL9, CXCL10, and CXCL11 were prominent in patients with AEs over G2 levels. As these chemokines recruit Th1, Th17, and activated CD8+ T cells, increased serum levels of these chemokines might correlate with the positive feedback of inflammatory reactions related to AEs.